La traduction française moderne de «Tirant lo Blanch»: méthode et problèmes - Barberà, Jean Marie (Caplletra. Revista Internacional de Filologia, 1997)
When reading a good translation we seldom consider how many hours the translator has silent on it or how difficult the text was for him. Jean Marie Barberà's paper aims at showing us, on the basis of concrete examples, how extremely difficult is to translate a literary work such as Tirant lo Blanch into a language as close to Catalan as French. The author exposes the difficulties that have arisen in the translation of Martorell's novel by showing us the original version of a fragment followed by the French version; afterwards, we will find a thorough comment on every detail which appears in the translation of different words or fragments which cannot have a natural or simple adaptation into French.